#TITLE_ALTERNATIVE# - WULANDARI (NIM 23406009), ESTI
The quality of working life is a terminology used to reflect the feeling of workers on the relationship between employment and occupational environment. The aim of this study is to find out the effect of the characteristic of flexible employment on the quality of working life. As a sample of the flexible employment, insurance agent is being used as respondent of this study. The job characteristics used in the study are based on the Theory of Job Characteristics pointed out by Hackman and Oldham (1980): variety of skills, task identity, task significance, autonomy, and feedback. Considering the freedom to arrange time, place and way for doing job, insurance agent employment is belongs to flexible working. But there is no complete information about job characteristics of insurance agents and their quality of working life. Two main research questions in the study are: (1) How are the job characteristics of insurance agents according to the Theory of Job Characteristics? and (2) How is the effect of job characteristics of insurance agents on their quality of working life?. To answer the two research questions, systematical stages are being done: (1) identifying variables of the study, (2) designing instruments of the study, (3) collecting data, and (4) processing and analyzing data. The data collection is done by spreading questionnaires to 108 insurance agents of 6 insurance firms in Bandung. To design the questionnaires, researcher conducting interviews with 25 representatives of insurance agents to understand the real system. Factor Analysis and Multiple Linear Regression is being used to process and analyze the data. Results of the data processing indicate that insurance agents have a variety of skill levels and high autonomy, indicating by score over 6 (on 7 scales). Task significance, feedback from job, and task identity of the insurance agents are similarly at adequate high level, indicating by score 5 (on 7 scales). Only variety of skills and task significance significantly contribute in determining the quality of insurance agents' working life. Level of significance used in this study is t-value < 0.05 (95% of confidence intervals). The result shows us that task significance is a job characteristic that give most significant effect on the quality of the insurance agents' working life. Based on the result of data processing, it is necessary to increase the awareness of insurance agents concerning the significance of work, which means management of the insurance firms should put more effort on doing that. Efforts that can be sought are: (1) providing the occupation-related training, (2) designing the occupational feedback channels, and (3) selecting the insurance agents that will be recruited by firms.